Pengaruh Penambahan Skim terhadap Karakteristik Dadih Susu Sapi yang Dibuat dalam Ruas Bambu Wuluh (Schizostachyum silicatum) di Bali - Ulfa, Mariya; Sugitha, I Made; Trisna Darmayanti, Luh Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 2 (2020): Jurnal ITEPADO - 10.24843/itepa.2020.v09.i02.p11, 2020)
This study aims to determine the effect of skim additional on the characteristics and the amount of the right skim additional of cow milk dadih made in wuluh bamboo (Schizostachyum bluneiness) tubes. The completely randomized design with 5 levels of skim addition treatment were : 4%, 6%, 8%, 10% and 12%. The treatment was repeated 3 times for obtain 15 experimental units. The data were analyzed by variance, and the significant effect of the treatment was followed by Duncan. The additional of skim has effect to yield, water content, pH, total acid, total microbes, total lactic acid bacteria (LAB) and has effect to scoring test of aroma, taste and overall acceptance by hedonic test, but doesn’t significantly affect scoring test of color and texture. The addition of 10% skim produces the best characteritics with yield 65,31%, water content 63,72%, pH 5,50, total lactic acid 1,31%, total bacterial colony 4,38 x 109CFU/g, total lactic acid bacteria (LAB) 3,42 x 109 CFU/g, color cream, typical aroma of fermented milk, solid texture, sour taste and rather dislike on overall acceptance. Keywords : cow milk dadih, skim milk, wuluh bamboo.